Solve the linear equation.
-2x - 2 + 7(x + 1) = 2x - 4

Question

Asked 4/20/2013 1:50:02 PM

Updated 8/5/2014 10:56:52 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [8/5/2014 10:56:09 PM], Confirmed by andrewpallarca [8/5/2014 10:56:49 PM]

Expert answered|emdjay23|Points 1159|

Question

Asked 4/20/2013 1:50:02 PM

Updated 8/5/2014 10:56:52 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [8/5/2014 10:56:09 PM], Confirmed by andrewpallarca [8/5/2014 10:56:49 PM]

Rating

3

6x - 7 + 3(x + 1) = 4x - 6;

6x - 7 + 3x + 3 = 4x - 6;

9x - 4 = 4x - 6;

9x - 4x = -6 + 4;

5x = -2;

x = -2/5

6x - 7 + 3x + 3 = 4x - 6;

9x - 4 = 4x - 6;

9x - 4x = -6 + 4;

5x = -2;

x = -2/5

Added 8/5/2014 10:56:52 PM

This answer has been confirmed as correct and helpful.

Evaluate the algebraic expression for the given value or values of the variable(s).
3x - 4;x = -4 (Points : 2) Here are the multiple choices: -16
16
-8
8 **Weegy:**
3x - 4;x = -4;
3(-4) - 4 = -12 - 4 = -16
(More)

Question

Expert Answered

Updated 8/5/2014 10:58:08 PM

0 Answers/Comments

6x + 2; x = 2 **Weegy:**
6x + 2; x = 2;
6(2) + 2 = 12 + 2 = 14
(More)

Question

Expert Answered

Updated 8/5/2014 10:59:10 PM

0 Answers/Comments

Write the algebraic expression without parentheses.
-(-2 + 7y) . Here are the multiple choices: -2 + 7y
2 - 7y
14y
2 + 7y **Weegy:** -(-2 + 7y), the algebraic expression is: 2 - 7y (More)

Question

Expert Answered

Updated 7/15/2014 9:13:51 AM

0 Answers/Comments

Simplify the algebraic expression.
-3(2x - 5) - 4x + 8 . HERE ARE THE MULTIPLE CHOICES: -10x + 23
2x + 23
10x + 23
-10x - 7 **Weegy:**
-3(2x - 5) - 4x + 8,
-6x + 15 - 4x + 8
= -10x + 23
(More)

Question

Expert Answered

Updated 6/13/2014 11:02:08 AM

0 Answers/Comments

Solve this proportion: x + 1 over 6 and x + 2 over 4. Here are the multiple choices: { - 4} {3} {1/2} { - 6}
User: That is incorrect, please look at the multiple choices. **Weegy:** How to Construct Better
Multiple-Choice Tests
This section is intended for school, college, [ [ and university teachers.
When to use multiple-choice: advantages and disadvantages
How to write a good multiple-choice question
Advanced techniques for innovative multiple-choice questions
Advanced techniques for testing higher level thinking
Question Arrangement on Tests.
Multiple-Choice Construction Checklist
Frequently Asked Questions about Multiple-choice
Multiple-Choice Glossary
References: Useful textbooks and relevant websites
] ] (More)

Question

Expert Answered

Updated 8/6/2014 9:35:18 PM

1 Answer/Comment

-4 is the answer for x + 1 over 6 and x + 2 over 4.

(x+1)/6=(x+2)/4

(x+1)/3=(x+2)/2

2*(x+1)/3=x+2

2x+2=3(x+2)

2x+2=3x+6

3x-2x=2-6

x=-4.

(x+1)/6=(x+2)/4

(x+1)/3=(x+2)/2

2*(x+1)/3=x+2

2x+2=3(x+2)

2x+2=3x+6

3x-2x=2-6

x=-4.

Added 8/6/2014 9:27:22 PM

This answer has been confirmed as correct and helpful.

27,099,195

questions answered

There are no comments.